Ultrasound Findings in Dengue Fever: A Single Center Study - Zahid Bashir, Asad Ullah Kamran, Harris Saeed, Romale Nazir, Sehrish Patras, Khurram Mehmood, Muhammad Zulqarnain, (Pakistan Journal of Medical & Health Sciences, 2022)
Dengue fever is the most quickly spreading and transmitted mosquito bite disease, with an annual incidence of around 50 million people. Plasma leakage during dengue fever results in the development of serious consequences. Objective: To determine the ultrasonography findings used for diagnosing plasma leakage in patients managed with diagnosis of dengue fever Study Design: Cross sectional descriptive study Setting: Department of Radiologist, Bahawal victoria hospital Bahawalpur. Duration of Study: 4 months (August to November, 2021) Methodlogy: All the patients of dengue fever admitted in the dengue isolation ward of the hospital, diagnosed using anti-dengue serology were enrolled to be included in the study after a written informed consent from the parents or attendants. All these patients were sent to a consultant radiologist for ultrasound abdomen to look for ascites, pleural effusion, gall bladder thickness, liver size, hepatomegaly, spleen size and splenomegaly. Results: Dengue fever is one of the most frequent diseases in our region of the globe. It manifests itself in a variety of ways, but early detection and treatment can help to reduce case fatality rates. This demonstrates the ultrasonography results that might be observed in Dengue Fever patients showing capillary leakage are seen in around thirty percent of the patients. Further studies should be done to correlate ultrasonography findings with the severity of dengue. Conclusion: Dengue fever is one of the most frequent diseases in our region of the globe. It manifests itself in a variety of ways, but early detection and treatment can help to reduce case fatality rates. This demonstrates the ultrasonography results that might be observed in Dengue Fever patients showing capillary leakage are seen in around thirty percent of the patients. Further studies should be done to correlate ultrasonography findings with the severity of dengue.